2016
DOI: 10.1128/jvi.02985-15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Divergent Immunogenicity of Two Pediatric Tick-Borne Encephalitis Virus Vaccines

Abstract: Studies evaluating the immunogenicity of two pediatric tick-borne encephalitis virus (TBEV) vaccines have reported contradictory results. These vaccines are based on two different strains of the European TBEV subtype: FSME-Immun Junior is based on the Neudörfl (Nd) strain, whereas Encepur Children is based on the Karlsruhe (K23) strain. The antibody (Ab) response induced by these two vaccines might be influenced by antigenic differences in the envelope (E) protein, which is the major target of neutralizing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…This amino acid is found in the K23 vaccine strain (GenBank accession no. AM600965.1) [44]; however, this is the only TBEV strain found in the database (GenBank) sequenced that contains this amino acid in that position (www.viprbrc. org).…”
Section: Discussionmentioning
confidence: 99%
“…This amino acid is found in the K23 vaccine strain (GenBank accession no. AM600965.1) [44]; however, this is the only TBEV strain found in the database (GenBank) sequenced that contains this amino acid in that position (www.viprbrc. org).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FSME-IMMUN® was shown to the neutralize Swedish strains better compared to Encepur®, where some sera showed borderline neutralizing titers after Encepur vaccination and one serum did not neutralize 93/783 at all. A previous study found that the amino acid K52 is very important for efficient neutralization by Encepur®, this amino acid is found in the K23 vaccine strain [53], however, this is the only TBEV strain found in the gene bank database sequenced that contains this amino acid in that position (www.viprbrc.org). This could also explain why the Swedish isolates which lacks the K52 are not neutralized as efficiently by Encepur®.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one mutation in the EDI/EDII hinge region in the K23 vaccine seed virus (used for manufacturing of Encepur) was identified to be responsible for reduced VN antibody titers against heterologous Neudoerfl virus (vaccine strain used for manufacturing of FSME-IMMUN) of sera received from children vaccinated with Encepur Children. In contrast, sera of children immunized with FSME-IMMUN Junior showed comparable high levels of VN antibodies against both TBEV strains [ 136 ].…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 99%